Edukasi Gizi Seimbang dan Deteksi Dini Tanda Bahaya Pada Kehamilan - Raehan Raehan; Nur Anita; Tri Noviyanti Mansyur; Yesi Gusnawati (Yayasan Inspirasi El Burhani, 2026)
Introduction: Pregnancy is a critical period that greatly influences the health outcomes of both the mother and the fetus. Adequate maternal nutrition plays a crucial role in supporting fetal growth and development, preventing pregnancy complications, and reducing the risk of stunting. In addition to nutritional adequacy, early detection of danger signs during pregnancy is an important preventive measure to reduce maternal morbidity and mortality. However, limited knowledge among pregnant women and their families regarding balanced nutrition and pregnancy danger signs often leads to delays in seeking appropriate medical care. Therefore, educational interventions are needed to improve awareness and understanding of these issues. Objective: This community service activity aimed to improve the knowledge and awareness of pregnant women regarding balanced nutrition and the early detection of pregnancy danger signs in the working area of Lembang Public Health Center. Method: This activity was conducted through health education sessions involving lectures, interactive discussions, and question-and-answer sessions. Educational materials focused on balanced nutrition during pregnancy and the identification of pregnancy danger signs. The effectiveness of the education was evaluated using a pre-test and post-test to measure participants’ knowledge improvement. In addition, health screening was conducted, including hemoglobin examination, measurement of mid-upper arm circumference (MUAC), and blood pressure assessment to identify potential pregnancy risks. Result: The results showed a significant increase in participants’ knowledge regarding balanced nutrition, with average scores improving from 62% in the pre-test to 85% in the post-test. Understanding of pregnancy danger signs also increased from 58% to 88%. Furthermore, 90% of participants expressed commitment to regularly consuming iron tablets, and 85% were able to mention at least three pregnancy danger signs after the educational session. Screening results revealed that 20% of pregnant women were at risk of anemia, 15% had MUAC below 23.5 cm indicating risk of chronic energy deficiency, and two cases of hypertension were referred for further medical examination. Conclusion: The educational program on balanced nutrition and early detection of pregnancy danger signs was successfully implemented and resulted in improved knowledge and awareness among pregnant women. This activity contributes to strengthening promotive and preventive health efforts in improving maternal health outcomes and supporting safe pregnancies.